Lithium ion secondary battery and method for manufacturing same

By forming a porous coating on the electrodes of the lithium secondary battery and using high flash point flame retardant electrolytes, the problems of instability and insufficient electrolyte impregnation in the charging state of lithium secondary battery are solved, and higher stability is achieved and electrochemical properties.

CN119301797APending Publication Date: 2025-01-10LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380043958.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-12
Filing Date
2023-05-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Instability and ignition problems caused by the shrinkage or short circuit of the diaphragm in the charged state of lithium secondary batteries, and the flame retardant electrolyte is difficult to immerse evenly in conventional diaphragms, affecting the capacity, output and life of the battery.

Method used

A porous coating is used to form a porous coating on the electrode, including polymer particles or ceramic particles with an absolute value of zeta potential of more than 25mV, and a flame retardant solvent with a flash point of more than 100°C or no flash point and a flame retardant electrolyte with a flame retardant point of more than 100°C and a flame retardant electrolyte with a flash point of more than 100°C and a flame retardant electrolyte with a flash point of more than 100°C and no flash point, instead Traditional diaphragms ensure the insulation between the electrodes and the uniform impregnation of the electrolyte.

Benefits of technology

It effectively suppresses short circuits and ignition caused by diaphragm shrinkage and high temperature, improves the stability and electrochemical characteristics of the battery, such as capacity, output and life characteristics, and significantly improves the overall performance of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301797A_ABST
    Figure CN119301797A_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery comprising: an electrode assembly comprising an electrode and a porous coating layer formed on the electrode; and a flame-retardant electrolyte containing a flame-retardant solvent defined as a predetermined flash point and a lithium salt, in which the porous coating layer contains polymer particles or ceramic particles having a zeta potential absolute value of 25 mV or more, thereby improving stability while maintaining various properties of the lithium secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0069165 filed on June 7, 2022, Korean Patent Application No. 10-2022-0073089 filed on June 15, 2022, and Korean Patent Application No. 10-2023-0061581 filed on May 12, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to a lithium secondary battery and a method for manufacturing the same. [Background technology]

[0004] In recent years, as the application fields of lithium secondary batteries have rapidly expanded to power storage supply for large-area equipment such as automobiles and power storage devices, and power supply for electronic equipment such as electricity, electronics, communications and computers, the demand for lithium secondary batteries with high capacity, high output, long life and high stability has increased.

[0005] Lithium secondary batteries are generally configured to include a positive electrode, a negative electrode, a separator and an electrolyte, and it is known in the relevant technical field to include a positive electrode capable of generating oxygen due to an unstable structure in a charged state. Since the risk of fire is great when oxygen is generated in this way, attempts have been made to study and develop methods for enhancing the safety of lithium secondary batteries.

[0006] In lithium secondary batteries, the separator is used to ensure electrical insulation between the positive electrode and the negative electrode, and a film made of polyolefin is generally used as the separator. However, this separator is easy to shrink under high temperature conditions, so it cannot ensure insulation between the positive electrode and the negative electrode. In addition, when the folding or mismatch of the separator occurs during the assembly of the lithium secondary battery, the battery works normally in the initial stage, but over time, lithium dendrites, etc. are generated, resulting in a short circuit. When electrical insulation between the positive and negative electrodes becomes impossible, a short circuit may occur, which may interact with the oxygen generated by the unstable positive electrode to cause a fire. In other words, when a lithium secondary battery in a charged state is short-circuited due to high temperature or impact applied during the process, there is a problem of lithium secondary battery catching fire.

[0007] In addition, the electrolyte of the known lithium secondary battery contains a highly volatile and flammable solvent, but there is a problem of easy fire. In order to solve this problem, a flame retardant electrolyte containing a flame retardant solvent can be used, but there is a problem that such a flame retardant electrolyte cannot be well impregnated into a conventional separator. If the electrolyte is not well impregnated into the lithium secondary battery, the lithium ions cannot be satisfactorily transmitted, which leads to the problem that the capacity, output and life characteristics of the lithium secondary battery are all deteriorated. In addition, if the electrolyte is not well impregnated into the lithium secondary battery, there is a problem of uneven reaction between the electrode and the electrolyte, thereby generating dendrites and causing a short circuit.

[0008] Therefore, in order to solve these problems, attempts have been made to study and develop methods of improving stability while maintaining various properties of lithium secondary batteries. [Summary of the invention]

[0009]

Technical issues

[0010] An object of the present invention is to provide a lithium secondary battery and a method for manufacturing the same which not only improves stability and suppresses ignition but also improves electrolyte impregnation and improves various characteristics.

[0011]

Technical solution

[0012] According to the present invention, a lithium secondary battery is provided, comprising: an electrode assembly comprising an electrode and a porous coating formed on the electrode; and a flame retardant electrolyte comprising a flame retardant solvent having a flash point of 100° C. or above or having no flash point and a lithium salt, wherein the porous coating comprises polymer particles or ceramic particles having a zeta potential absolute value of 25 mV or above.

[0013] In addition, according to the present invention, a method for manufacturing a lithium secondary battery is provided. The manufacturing method may include the following steps: forming a porous coating layer containing polymer particles or ceramic particles having an absolute value of zeta potential of 25 mV or more on an electrode; forming an electrode assembly containing an electrode coated with the porous coating layer; and impregnating the electrode assembly with a flame retardant electrolyte containing a flame retardant solvent having a flash point of 100° C. or more or having no flash point and a lithium salt.

[0014]

Beneficial Effects

[0015] In the lithium secondary battery of the present invention, a porous coating formed on an electrode is used instead of an existing separator to ensure electrical insulation between a positive electrode and a negative electrode. In an electrode assembly including such a porous coating, the occurrence of a short circuit due to shrinkage of an existing separator can be suppressed, and ignition due to high temperature, external impact, etc. can be reduced.

[0016] In addition, the lithium secondary battery includes a flame retardant electrolyte to inhibit fire, and the flame retardant electrolyte is also well impregnated into the electrode assembly including the porous coating, so that a uniform reaction can occur over the entire electrode. Therefore, various properties of the lithium secondary battery such as capacity, output and life characteristics can be improved. In addition, in the lithium secondary battery, the electrolyte is well impregnated into the electrode assembly, and a uniform reaction occurs between the electrode and the electrolyte, thereby inhibiting the occurrence of dendrites and short circuits.

Brief Description of the Drawings

[0017] Figure 1 is a schematic diagram showing an electrode assembly of a lithium secondary battery according to an embodiment of the present invention;

[0018] Figures 2 to 5 Hot box test results of the lithium secondary batteries of Examples 1 to 3 and Comparative Example 1 are shown respectively. [Specific implementation method]

[0019] The terms or words used in this specification and claims should not be construed as limited to the ordinary or dictionary meanings, but should be interpreted with meanings and concepts consistent with the technical concept of the present invention based on the principle that the inventor can appropriately define the concepts of the terms in order to appropriately explain his invention in the best manner.

[0020] It should be understood that the terms "comprising", "containing" or "having" used in this document specify the presence of stated features, integers, steps, components or their combinations, but do not exclude the presence or addition of one or more other features, integers, steps, components or their combinations.

[0021] According to one embodiment of the present invention, a lithium secondary battery is provided, comprising: an electrode assembly comprising an electrode and a porous coating formed on the electrode; and a flame retardant electrolyte comprising a flame retardant solvent having a flash point of 100° C. or above or having no flash point and a lithium salt, wherein the porous coating comprises polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or above.

[0022] As described above, the lithium secondary battery of one embodiment is configured to form a porous coating that substantially replaces the existing separator on the electrode of the positive electrode or the negative electrode in the electrode assembly, wherein the porous coating contains polymer particles or ceramic particles having an absolute value of zeta potential above a certain level. The absolute value of zeta potential can define the surface polarity of polymer particles or ceramic particles, and an absolute value above a certain level can mean that the surface polarity increases.

[0023] In addition, the flame retardant solvent contained in the battery of one embodiment has a higher polarity than the organic solvent contained in the electrolyte for general lithium ion batteries. Therefore, due to the combination of the porous coating layer containing particles with high surface polarity and the flame retardant solvent, excellent affinity between the flame retardant electrolyte and the electrode formed with the porous coating layer is achieved, thereby showing excellent impregnation of the porous coating layer with the flame retardant electrolyte, solving the problem of short circuit caused by thermal shrinkage of the existing separator.

[0024] Furthermore, a lithium secondary battery of one embodiment includes a flame retardant electrolyte containing a lithium salt and a flame retardant solvent having no flash point (substantially non-flammable) or a flash point of 100° C. or more. As a result, a porous coating can be uniformly impregnated with such a flame retardant electrolyte while suppressing ignition of the battery.

[0025] In this way, a lithium secondary battery of one embodiment includes a porous coating layer instead of a separator and a predetermined flame-retardant electrolyte, thereby suppressing short circuit and fire and exhibiting excellent stability, and the flame-retardant electrolyte is uniformly impregnated into the porous coating layer, thereby improving various electrochemical characteristics such as capacity, output or life characteristics.

[0026] Hereinafter, a lithium secondary battery and a method for manufacturing the same according to an embodiment of the present invention will be described in more detail.

[0027] Electrode assembly

[0028] A lithium secondary battery according to one embodiment basically comprises an electrode assembly. Figure 1 As shown, the electrode assembly comprises: electrodes including a positive electrode and a negative electrode, and a porous coating formed on the electrodes, such as the positive electrode and / or the negative electrode, and the porous coating comprises polymer particles or ceramic particles having an absolute value of zeta potential of 25 mV or more.

[0029] At this time, the zeta potential of polymer particles or ceramic particles is a physical property that reflects the surface polarity of these particles and defines the electrostatic repulsion or dispersibility between particles. Polymer particles or ceramic particles with a large absolute value of zeta potential can be evenly dispersed on the positive electrode active material layer, thereby showing satisfactory uniform coating properties, and a large number of small and uniform pores that allow lithium ions to pass between these particles can be defined. In addition, due to particles that meet such zeta potential, the porous coating can show excellent impregnation properties for a flame retardant electrolyte containing a flame retardant solvent. The combination of a porous coating and a flame retardant electrolyte enables a lithium secondary battery of an embodiment to exhibit the above-mentioned excellent properties.

[0030] The zeta potential of the polymer particles or ceramic particles can be measured, for example, by an electrophoretic light scattering method using a dynamic light scattering device. In this case, the zeta potential of the polymer particles or ceramic particles can be measured in a state where the particles are dispersed in water or an alcohol solvent without using an additional dispersant. In a specific example, the zeta potential can be measured in a state where the polymer particles or ceramic particles are dispersed in an aqueous solvent at a concentration of 0.1 wt % or less.

[0031] The absolute value of the zeta potential of the polymer particles or ceramic particles may be 25 mV or more, or 35 mV or more, or 45 mV or more, and 100 mV or less, or 90 mV or less, or 80 mV or less. Within this range, satisfactory coating properties of the coating slurry can be achieved, and high impregnation properties of the flame retardant electrolyte can be ensured, so that the battery of one embodiment can exhibit excellent stability and various electrochemical properties.

[0032] Specific examples of the polymer particles include at least one selected from the group consisting of polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, and polyphenylene sulfide.

[0033] In addition, specific examples of the ceramic particles include at least one selected from the group consisting of boehmite (γ-AlO(OH)), Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5 and MnO.

[0034] The zeta potential of polymer particles or ceramic particles can be controlled not only by the type of each particle, but also by the particle size or surface properties of these particles. Therefore, in order to achieve the zeta potential, dispersibility and suitable porosity of the porous coating of the polymer particles or ceramic particles, the particle size of the polymer particles or ceramic particles can be 50nm to 3μm, 50nm to 1.5μm or 100nm to 1μm.

[0035] In addition, as will be described in more detail below, in order to control the surface properties of the polymer particles or ceramic particles and thereby adjust the zeta potential, etc., the polymer particles or ceramic particles may be included in the coating slurry in a state of being surface-treated with oxygen plasma or ion beams.

[0036] Meanwhile, porous coating can be configured to include polymer binder and polymer particles or ceramic particles dispersed on polymer binder.At this point, polymer binder used herein can be a polymer of the same type as the binder included in the electrode active material layer, and its specific examples can include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, acrylonitrile-butadiene rubber, styrene-butadiene rubber or fluororubber, etc., and mixtures or copolymers of two or more selected from these polymers can also be used.However, those skilled in the art can obviously consider the type and characteristics of polymer particles or ceramic particles, the method for forming coating, etc. to determine the specific composition of polymer binder.

[0037] In addition, considering the excellent coatability of the above-mentioned coating slurry and the excellent dispersibility of the particles, the porous coating slurry may include the polymer binder and the polymer particles or ceramic particles in a weight ratio of 5:95 to 40:60, or 10:90 to 35:65.

[0038] From the perspective of excellent impregnation of flame retardant electrolyte and effective replacement of separator, the porous coating may have a thickness of 5 to 50 μm, or 10 to 45 μm, or 15 to 40 μm and include a plurality of pores having a diameter of 10 nm or more, or 20 nm to 3 μm, or 50 nm to 1 μm. At this time, the thickness of the porous coating may refer to the total thickness of the porous coating formed on the positive electrode and / or the negative electrode.

[0039] Meanwhile, the electrode assembly including the porous coating may include: for example, Figure 1 The illustrated positive electrode has a positive electrode tab protruding from a positive electrode current collector; the negative electrode has a negative electrode tab protruding from a negative electrode current collector; and a porous coating layer formed on the positive electrode or the negative electrode so as to be arranged between the positive electrode and the negative electrode.

[0040] In addition, the positive electrode and the negative electrode may include a positive electrode active material layer and a negative electrode active material layer formed on a positive electrode collector and a negative electrode collector, respectively. The above-mentioned porous coating layer may be formed on the positive electrode active material layer and / or the negative electrode active material layer, and may be arranged between the positive electrode active material layer and the negative electrode active material layer in a state of contacting these layers. In a more specific embodiment, as Figure 1 As shown, the porous coating layers may be formed on the positive electrode active material layer and the negative electrode active material layer, respectively, and the porous coating layer formed on the negative electrode active material layer and the porous coating layer formed on the positive electrode active material layer may contact each other.

[0041] Meanwhile, in the electrode assembly, the current collector of the positive electrode is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, the current collector can be formed of stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver, etc.

[0042] In addition, the positive electrode active material layer on the positive electrode current collector may include a positive electrode active material, a binder, and a conductive material.

[0043] At this time, the positive electrode active material can be a material capable of reversibly intercalating and deintercalating lithium. Among them, the positive electrode active material may specifically include lithium metal oxides containing lithium and at least one metal such as cobalt, manganese, nickel, or aluminum. More specifically, the lithium metal oxides may include: lithium manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (e.g., LiCoO2, etc.), lithium nickel-based oxides (e.g., LiNiO2, etc.), lithium nickel manganese-based oxides (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1)), lithium manganese cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), lithium nickel manganese cobalt-based oxides (e.g., Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, and p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, and p1 + q1 + r1 = 2), etc.), lithium nickel cobalt transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r2 M s2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are the atomic fractions of the respective independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1 and p2 + q2 + r2 + s2 = 1), etc.), lithium iron phosphate (e.g., Li 1+a Fe1-x M x (PO 4-b )X b (wherein M is at least one selected from Al, Mg and Ti, X is at least one selected from F, S and N, -0.5≤a≤+0.5, 0≤x≤0.5, 0≤b≤0.1), etc., any one or more compounds thereof can be used.

[0044] Among these materials, lithium composite metal oxides may include LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2、Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.) or lithium nickel manganese cobalt aluminum oxide (e.g., Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O2) or lithium iron phosphate (for example, LiFePO4), etc., any one of which or a mixture of two or more thereof can be used.

[0045] Among them, a positive electrode active material having a nickel content of 80 atomic % or more may be used because the capacity characteristics of the battery can be maximized. For example, the lithium transition metal oxide may include an oxide represented by the following Chemical Formula 1.

[0046] [Chemical formula 1]

[0047] Li x Ni a Co b M 1 c M 2 d O2

[0048] In Chemical Formula 1, M 1It may be at least one selected from Mn and Al or a combination thereof.

[0049] M 2 It may be at least one selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S.

[0050] x represents the atomic fraction of lithium in the lithium transition metal oxide, and it can be 0.90 ≤ x ≤ 1.1, or 0.95 ≤ x ≤ 1.08, or 1.0 ≤ x ≤ 1.08.

[0051] a represents the atomic fraction of nickel among the metal elements other than lithium in the lithium transition metal oxide, and it can be 0.80 ≤ a < 1.0, or 0.80 ≤ a ≤ 0.95, or 0.80 ≤ a ≤ 0.90. When the nickel content satisfies the above range, high-capacity characteristics can be achieved.

[0052] b represents the atomic fraction of cobalt among the metal elements other than lithium in the lithium transition metal oxide, and it can be 0 < b < 0.2, 0 < b ≤ 0.15, or 0.01 ≤ b ≤ 0.10.

[0053] c represents the atomic fraction of M among the metal elements other than lithium in the lithium transition metal oxide 1 and it can be 0 < c < 0.2, 0 < c ≤ 0.15, or 0.01 ≤ c ≤ 0.10.

[0054] d represents the atomic fraction of M among the metal elements other than lithium in the lithium transition metal oxide 2 and it can be 0 ≤ d ≤ 0.1 or 0 ≤ d ≤ 0.05.

[0055] Based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can be 60 to 99% by weight, 70 to 99% by weight, or 80 to 98% by weight.

[0056] The binder is a component that helps the binding between the active material and the conductive material, etc., and the binding with the current collector. Examples of the binder can include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, nitrile rubber, styrene-butadiene rubber, or fluororubber, etc. A mixture or copolymer of two or more of them can be used.

[0057] Generally, based on the total weight of the positive electrode active material layer, the content of the binder can be 1 to 20% by weight, 1 to 15% by weight, or 1 to 10% by weight.

[0058] The conductive material is a component that further improves the conductivity of the positive electrode active material. The conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, a conductive material such as carbon powder, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black can be used; graphite powder, such as natural graphite, artificial graphite or graphite with a fully developed crystal structure; conductive fibers such as carbon fibers or metal fibers; fluorocarbon powder; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.

[0059] Generally, the content of the conductive material may be 1 to 20 wt %, 1 to 15 wt %, or 1 to 10 wt % based on the total weight of the positive electrode active material layer.

[0060] Meanwhile, the negative electrode in the electrode assembly may include a negative electrode collector, a negative electrode active material layer containing a negative electrode active material, a binder, a conductive material, and the like, and optionally the above-mentioned porous coating layer.

[0061] The thickness of the negative electrode collector is generally 3 to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc. can be used. In addition, similar to the positive electrode collector, the negative electrode collector can be formed with fine concave-convex on its surface to enhance the adhesion of the negative electrode active material. For example, the negative electrode collector can be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven fabric structure.

[0062] The negative electrode active material may include at least one selected from the group consisting of lithium metal, carbon materials capable of reversibly intercalating / deintercalating lithium ions, metals or alloys of lithium and these metals, metal composite oxides, materials that can be doped and dedoped with lithium, and transition metal oxides.

[0063] As a carbon material capable of reversibly embedding / de-embedding lithium ions, any carbon material can be used without particular limitation, as long as it is a carbon-based negative electrode active material commonly used in lithium ion secondary batteries, and as a typical example, crystalline carbon and / or amorphous carbon can be used. An example of crystalline carbon can be graphite, such as irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, and an example of amorphous carbon can be soft carbon (low temperature calcined carbon) or hard carbon, mesophase pitch carbide and fired coke.

[0064] As the metal or an alloy of lithium and these metals, metals selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of lithium and these metals can be used.

[0065] One selected from the group consisting of PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups I, II, and III of the periodic table, or halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) can be used as a metal composite oxide.

[0066] Materials that can be doped and de-doped with lithium can include Si, SiO x (0 < x ≤ 2), Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, and Sn-Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn). A mixture of SiO2 and at least one of them can also be used. The element Y can be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0067] Transition metal oxides can include lithium-containing titanium composite oxides (LTO), vanadium oxides, and lithium vanadium oxides, etc.

[0068] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be 60 to 99 wt%, or 70 to 99 wt%, or 80 to 98 wt%.

[0069] Meanwhile, the types of binders and conductive materials that may be included in the negative electrode active material layer and the contents of these materials are substantially the same as those described above for the positive electrode active material layer, and additional description thereof will be omitted below.

[0070] Figure 1 An example of an electrode assembly including a positive electrode, a negative electrode, and a porous coating layer formed on these electrodes is shown in FIG. Figure 1 In the electrode assembly, the conductive surface of the negative electrode (see Figure 1 The "A" in (A) may also include an insulating layer covering the positive electrode at a position corresponding to the positive electrode tab of the positive electrode.

[0071] In a general lithium secondary battery, the negative electrode is generally formed to have a larger area than the positive electrode in consideration of the irreversible capacity in the initial stage of charge and discharge. However, due to this area difference, the electrode assembly is curled during the manufacturing process of the lithium secondary battery, and the positive electrode tab is bent so that the positive electrode tab contacts the conductive surface of the negative electrode ( Figure 1 ), which may cause a short circuit.

[0072] In this way, the conductive surface of the negative electrode ( Figure 1 The "A" in the figure may be the negative electrode side surface corresponding to the positive electrode tab. In addition, due to the area difference between the positive electrode and the negative electrode, an exposed surface where the negative electrode current collector is exposed without forming the negative electrode active material layer and the porous coating may be generated in the negative electrode surface. This exposed surface may also become a conductive surface of the negative electrode that may short-circuit with the positive electrode tab ( Figure 1 in the text box).

[0073] When an insulating layer is further formed to cover the conductive surface of the negative electrode ( Figure 1 When the positive electrode ear is bent, a short circuit caused by bending of the positive electrode ear can be prevented.

[0074] Meanwhile, the thickness of the insulating layer may be 100 μm or less, or 10 to 100 μm, or 30 to 70 μm. When the thickness of the insulating layer satisfies the above range, sufficient insulating effect may be obtained without interfering with other components of the electrode assembly.

[0075] In addition, such an insulating layer can be formed by coating an insulating liquid or by attaching an insulating tape, and the insulating liquid can contain a solvent and an insulating polymer. In addition, the insulating tape can contain polyimide.

[0076] In addition, the insulating liquid may contain a polymer resin and ceramic particles. The polymer resin may include at least one selected from the group consisting of polyethylene, polypropylene, polybutylene, polystyrene, polyethylene terephthalate, natural rubber and synthetic rubber. Among them, polyethylene, polypropylene, etc. with excellent insulation and electrolyte resistance can be used.

[0077] Flame retardant electrolyte

[0078] On the other hand, a lithium secondary battery of one embodiment includes the above-mentioned electrode assembly, and a flame retardant electrolyte containing a flame retardant solvent having a flash point of 100°C or more or having no flash point and a lithium salt. Such a flame retardant solvent may include a substantially non-flammable organic solvent having no flash point, and an organic solvent having a high flash point and low volatility of 100°C or more, or 100 to 250°C, or 110 to 200°C. A lithium secondary battery of one embodiment includes a flame retardant electrolyte containing such a flame retardant solvent and a lithium salt, thereby exhibiting excellent safety and stability. In addition, since the flame retardant electrolyte can be uniformly impregnated into the above-mentioned porous coating, excellent electrochemical characteristics of the lithium secondary battery can be achieved. The flash point of the flame retardant solvent can be measured using a closed tester or an open tester according to the standard method of ASTM D93 or ASTM D1310.

[0079] In a specific example, the flame retardant solvent may be an organic solvent having a functional group selected from the group consisting of a functional group that can contribute to the low volatility and flame retardancy or non-flammability of the organic solvent, such as a sulfone functional group, a fluorine-containing functional group such as a fluorine-substituted hydrocarbon group, a phosphorus-containing functional group such as a phosphate group or a phosphonate group, and a nitrile functional group. More specifically, the flame retardant solvent may include at least one organic solvent selected from the group consisting of a sulfone compound, a nitrile compound, a phosphoric acid compound, and a fluorine-substituted carbonate compound.

[0080] Among them, the sulfone compound may include at least one selected from the group consisting of cyclic sulfone compounds or linear sulfone compounds, specifically, the sulfone compound may include at least one selected from the group consisting of cyclopentane sulfone, ethyl methyl sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl isopropyl sulfone, ethyl isobutyl sulfone, isopropyl isobutyl sulfone, isopropyl sec-butyl sulfone and butyl isobutyl sulfone.

[0081] In addition, the nitrile compound may include at least one selected from the group consisting of malononitrile, succinonitrile, glutaronitrile, adiponitrile, suberonitrile, and sebacononitrile.

[0082] In addition, the phosphoric acid compound may include at least one selected from the group consisting of dimethyl methylphosphonate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl ethylphosphonate, dimethyl methylphosphonate, dimethyl (2-methoxyethoxy)methylphosphonate, diethyl (2-methoxyethoxy)methylphosphonate and triphenyl phosphate.

[0083] In addition, the fluorine-substituted carbonate compound may include at least one selected from the group consisting of di(2,2,3,3-tetrafluoropropyl) carbonate, methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, propyl 2,2,2-trifluoroethyl carbonate, methyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, ethyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, di(2,2,2-trifluoroethyl) carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoroisopropyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolane-2-one and di(2,2,3,3-pentafluoropropyl) carbonate.

[0084] Meanwhile, the lithium salt contained in the flame retardant electrolyte serves as a medium for transmitting ions in the lithium secondary battery. For example, the lithium salt may include Li + as cations, and may include a group consisting of F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 -CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - At least one of the group consisting of is used as an anion.

[0085] Specifically, the lithium salt may include a lithium salt selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2), at least one of the group consisting of, but in view of excellent stability, preferably including LiN(SO2CF3)2. In addition to these, lithium salts commonly used in electrolytes of lithium secondary batteries can also be used without particular limitation.

[0086] The concentration of the lithium salt can be appropriately changed within a generally available range, but in order to obtain the best effect of forming an anticorrosive film on the electrode surface, the lithium salt can be included in the flame retardant electrolyte at a concentration of 0.5M to 6M, 1M to 3M, or 1M to 2.5M in the electrolyte. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics of the lithium secondary battery during high temperature storage is sufficient, and the viscosity of the flame retardant electrolyte is appropriate, thereby improving the impregnation of the flame retardant electrolyte.

[0087] In addition, the flame retardant electrolyte can prevent the electrolyte from decomposing and causing negative electrode collapse in a high power environment, or can optionally further contain electrolyte additives in consideration of low temperature high rate discharge characteristics, high temperature stability, and the effect of preventing overcharge or suppressing battery expansion at high temperature.

[0088] Representative examples of the electrolyte additive include at least one selected from the group consisting of cyclic carbonate compounds, halogenated carbonate compounds, sultone compounds, sulfate ester (salt) compounds, phosphate ester (salt) compounds, borate ester (salt) compounds, nitrile compounds, benzene compounds, amine compounds, silane compounds and lithium salt compounds.

[0089] Among them, the cyclic carbonate compounds may include vinylene carbonate (VC) or vinyl ethylene carbonate. In addition, the halogenated carbonate compounds may include fluoroethylene carbonate (FEC). In addition, the sultone compounds may include at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethane sultone, 1,3-propylene sultone (PRS), 1,4-butene sultone and 1-methyl-1,3-propylene sultone. Sulfate ester (salt) compounds may include ethylene sulfate (Esa), trimethylene sulfate (TMS) or methyl trimethylene sulfate (MTMS), and phosphate ester (salt) compounds may include at least one compound selected from the group consisting of difluorobisoxalate lithium phosphate, difluoro lithium phosphate, tetramethyl trimethyl silyl phosphate and tris (2,2,2-trifluoroethyl) phosphate.

[0090] The borate ester compound may include tetraphenylborate, lithium difluoroborate oxalate (LiODFB) or lithium dioxalate borate (LiB(C2O4)2, LiBOB), and the nitrile compound may include at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, 2-fluorophenylacetonitrile and 4-fluorophenylacetonitrile. In addition, the benzene compound may include fluorobenzene, the amine compound may include triethanolamine or ethylenediamine, etc., and the silane compound may include tetravinylsilane. In addition, the lithium salt compound is a compound different from the lithium salt contained in the flame retardant electrolyte, wherein the lithium salt compound may include lithium nitrate, lithium difluorophosphate (LiDFP), LiPO2F2 or LiBF4, etc.

[0091] The electrolyte additive may be included in an amount of 0.1 to 10 wt %, or 0.2 to 8 wt %, or 0.5 to 8 wt %, based on the total weight of the flame-retardant electrolyte, thereby contributing to improvement of ion conductivity or cycle characteristics.

[0092] The lithium secondary battery may be formed by housing the electrode assembly in a case and injecting and impregnating a flame retardant electrolyte therein, and may be a cylindrical, prismatic, pouch or coin-type battery depending on the shape of the case, etc.

[0093] Method for manufacturing lithium secondary battery

[0094] Meanwhile, according to another embodiment of the present invention, a method for manufacturing the above-mentioned lithium secondary battery is provided. The manufacturing method comprises the following steps: forming a porous coating layer comprising polymer particles or ceramic particles having a zeta potential absolute value of 25 mV or more on an electrode; forming an electrode assembly comprising an electrode coated with the porous coating layer; and impregnating the electrode assembly with a flame retardant electrolyte comprising a flame retardant solvent having a flash point of 100°C or more or having no flash point and a lithium salt.

[0095] In another embodiment of the manufacturing method, since the method of forming each electrode can follow a general method, such as coating each active material layer-forming slurry composition on an electrode collector defining an electrode tab, followed by drying and rolling, additional description thereof will be omitted below.

[0096] Meanwhile, the step of forming a porous coating on the electrode can be carried out by a dry step or a wet step. For example, in the case of a dry step, it can be carried out by transferring a porous coating comprising polymer particles or ceramic particles and an optional polymer binder coated on a self-supporting or other substrate to an electrode (e.g., an electrode active material layer).

[0097] In addition, in the case of a wet process, it can be performed by a method of applying a slurry containing polymer particles or ceramic particles, a polymer binder, and a liquid medium onto an electrode (eg, an electrode active material layer) and drying it.

[0098] For the porous coating layer formed by the above method, an additional calendering step may be performed if necessary.

[0099] Meanwhile, the manufacturing method of other embodiments may further include a step of surface treating the polymer particles or ceramic particles by methods such as plasma, ion beam or surface coating to adjust the absolute value of the zeta potential to be above 25 mV. As described above, by such surface treatment, the surface properties of the polymer particles or ceramic particles can be controlled to meet the absolute value of the above zeta range.

[0100] At this time, the surface treatment step by plasma or the like may be performed before the polymer particles or ceramic particles are introduced into the porous coating layer-forming slurry, but may also be performed after the slurry is coated on the electrode.

[0101] A representative example of the surface treatment step may include a method of forming oxygen plasma in a reactor and treating the surface of the polymer particles or ceramic particles with it, thereby increasing the absolute value of the zeta potential of the particle surface.

[0102] After the porous coating layer is formed, the two electrodes may be joined and assembled to form an electrode assembly so that the porous coating layer is arranged between the electrodes. At this time, when the porous coating layer is formed on both electrodes, they may be joined and assembled to contact each other, and when the porous coating layer is formed on only one electrode, the porous coating layer may be joined and assembled to face the remaining electrode.

[0103] Subsequently, the step of impregnating the electrode assembly with the flame retardant electrolyte including the flame retardant solvent and the lithium salt may be performed by a general method of injecting the flame retardant electrolyte into a case accommodating the electrode assembly.

[0104] Hereinafter, the present invention will be described in more detail with reference to specific examples. However, the following examples are only for facilitating the understanding of the present invention and are not intended to limit the scope of the present invention.

[0105] Example

[0106] First, in the following examples, the zeta potential of polymer particles or ceramic particles was measured by an electrophoretic light scattering method using a dynamic light scattering device (product name: ELS-Z) at a temperature of 25° C. in a state where the polymer particles or ceramic particles were dispersed in an aqueous solvent at a concentration of 0.1 wt % or less.

[0107] In addition, the flash point of the (flame retardant) organic solvent contained in the (flame retardant) electrolyte is measured by a closed tester according to the standard method of ASTM D93. Specifically, the sample container is filled with the organic solvent sample, the container is covered and sealed with a lid, and then the sample container is heated at a constant rate according to the above standard method. During the heating process, the sample container is opened regularly to check whether a flame is generated, and the temperature at the time point when the flame is generated is measured as the flash point.

[0108] Example 1

[0109] Preparation of Li(Ni 0.8 Mn 0.1 Co 0.1 )O2 as the positive electrode active material with a thickness of 60 μm and artificial graphite as the negative electrode active material with a thickness of 75 μm.

[0110] Polymethyl methacrylate (PMMA) polymer particles with a Zeta potential of -50mV and a particle size of 1μm were placed and dispersed in an N-methyl-2-pyrrolidone (NMP) solvent so that the mass ratio of PMMA: hydrogenated nitrile rubber (H-NBR): polyvinylidene fluoride (PVDF) was 7:1:2, thereby preparing a porous coating slurry (solid content: 21 wt%). The resulting coating slurry was applied to the negative electrode rolled after forming the negative electrode active material layer, and then dried to form a porous coating on the negative electrode (the thickness of the porous coating was 30μm). The porous coating of the negative electrode and the positive electrode were arranged to contact each other to manufacture an electrode assembly.

[0111] LiN(SO2CF3)2 (LiFSI) was dissolved in a flame retardant solvent sulfolane (flash point: about 165°C) at a concentration of 1.5 M to prepare a flame retardant electrolyte. The electrode assembly was impregnated with the flame retardant electrolyte to manufacture a lithium secondary battery.

[0112] Example 2

[0113] Preparation of Li(Ni 0.8 Mn 0.1 Co 0.1 )O2 as the positive electrode active material with a thickness of 60 μm and artificial graphite as the negative electrode active material with a thickness of 75 μm.

[0114] The polymethyl methacrylate (PMMA) polymer particles with a Zeta potential of -50mV and a particle size of 1μm were placed and dispersed in an N-methyl-2-pyrrolidone (NMP) solvent, so that the mass ratio of PMMA: hydrogenated nitrile rubber (H-NBR): polyvinylidene fluoride (PVDF) was 7:1:2, thereby preparing a porous coating slurry (solid content: 21 wt%). The resulting coating slurry was applied to the positive electrode rolled after forming the positive electrode active material layer, and then dried to form a porous coating on the positive electrode (the thickness of the porous coating was 30μm). The porous coating of the positive electrode and the negative electrode were arranged to contact each other to manufacture an electrode assembly.

[0115] LiN(SO2CF3)2 (LiFSI) was dissolved in a flame retardant solvent sulfolane (flash point: about 165°C) at a concentration of 1.5 M to prepare a flame retardant electrolyte. The electrode assembly was impregnated with the flame retardant electrolyte to manufacture a lithium secondary battery.

[0116] Example 3

[0117] A lithium secondary battery was manufactured in the same manner as in Example 1 except that the positive electrode formed with a porous coating layer manufactured in Example 1 and the negative electrode formed with a porous coating layer manufactured in Example 2 were arranged so that the porous coating layers contacted each other to manufacture an electrode assembly.

[0118] Example 4

[0119] Nine negative electrodes formed with a porous coating layer and eight positive electrodes without a porous coating layer were manufactured in the same manner as in Example 1, respectively.

[0120] Eight positive electrodes were arranged and stacked between each of the nine negative electrodes formed with a porous coating. Polyimide insulating tape was attached to the area corresponding to the position where the positive electrode tab protruded on each stacked negative electrode ( Figure 1 “A” in the figure) to form an insulating layer (the thickness of the insulating layer was 60 μm), thereby manufacturing an electrode assembly.

[0121] LiN(SO2CF3)2(LiFSI) was dissolved in sulfolane (flash point: about 165°C) as a flame retardant solvent at a concentration of 1.5M and triethyl phosphate (TEP) at 1 wt% to prepare a flame retardant electrolyte. The electrode assembly was impregnated with the flame retardant electrolyte to manufacture a lithium secondary battery.

[0122] Example 5

[0123] In the same manner as in Example 2, eight positive electrodes formed with a porous coating layer and nine negative electrodes without a porous coating layer were manufactured, respectively.

[0124] Eight positive electrodes formed with porous coatings were arranged and stacked between each of the nine negative electrodes. Polyimide insulating tape was attached to the area corresponding to the position where the positive electrode tab protruded on each stacked negative electrode ( Figure 1 At this time, the insulating tape was pasted to cover not only the side of the negative electrode but also a part of the negative electrode plane where the negative electrode current collector was exposed without forming the negative electrode active material layer.

[0125] LiN(SO2CF3)2(LiFSI) was dissolved in sulfolane (flash point: about 165°C) as a flame retardant solvent at a concentration of 1.5M and triethyl phosphate (TEP) at 1 wt% to prepare a flame retardant electrolyte. The electrode assembly was impregnated with the flame retardant electrolyte to manufacture a lithium secondary battery.

[0126] Comparative Example 1

[0127] Preparation of Li(Ni 0.8 Mn 0.1 Co 0.1 )O2 as the positive electrode active material with a thickness of 60 μm and artificial graphite as the negative electrode active material with a thickness of 75 μm.

[0128] A separator made of polyolefin was inserted between the positive electrode and the negative electrode without the porous coating layer, thereby manufacturing an electrode assembly.

[0129] LiPF6 was dissolved in an organic solvent (ethylene carbonate (EC):ethyl methyl carbonate (EMC) = 30:70 volume ratio) at a concentration of 1 M to prepare a nonaqueous electrolyte.

[0130] The electrode assembly is immersed in a non-aqueous electrolyte to manufacture a lithium secondary battery.

[0131] Comparative Example 2

[0132] A lithium secondary battery was manufactured in the same manner as in Example 1 except that Al2O3 ceramic particles with a zeta potential of +20 mV and a particle size of 1 μm were used instead of polymethyl methacrylate (PMMA) polymer particles with a zeta potential of -50 mV and a particle size of 1 μm to form a porous coating on the negative electrode.

[0133] Reference Example 1

[0134] A lithium secondary battery was manufactured in the same manner as in Example 1, except that an insulating layer was not formed on the electrode assembly.

[0135] Experimental Example 1 - Evaluation of Thermal Stability

[0136] The lithium secondary batteries manufactured in Examples 1 to 3 and the lithium secondary battery manufactured in Comparative Example 1 were each subjected to a hot box test. The results are shown in FIG. Figures 2 to 5 .

[0137] Specifically, the hot box test was performed by increasing the temperature from 25°C at 5°C / min, maintaining the temperature at 100°C, 120°C, 140°C, 150°C, 160°C, 170°C and 180°C for 30 minutes each, and then increasing the temperature to 200°C at 2°C / min. Figures 2 to 5 The voltage-temperature change over time is shown. In addition, the ignition start temperature is shown in Table 1 below.

[0138] On the other hand, in the case of the lithium secondary battery of Comparative Example 2, since the flame retardant electrolyte was not impregnated and could not be fully charged, making it difficult to compare thermal safety under the same conditions, it was omitted from the thermal safety evaluation.

[0139] [Table 1]

[0140] Ignition start temperature (℃) Example 1 196 Example 2 192 Example 3 205 Comparative Example 1 170

[0141] like Figures 2 to 5 As shown in Table 1, it was confirmed that the lithium secondary batteries of Examples 1 to 3 had lower ignition start temperatures and exhibited improved thermal stability compared to Comparative Example 1.

[0142] Experimental Example 2 - Evaluation of various electrochemical properties

[0143] The initial capacity and capacity retention rate of each of the lithium secondary batteries manufactured in Examples 1 to 3 and the lithium secondary battery manufactured in Comparative Example 2 were measured, and the results are shown in Table 2 below.

[0144] The batteries manufactured in Examples 1 to 3 and Comparative Example 2 were each charged to 4.2 V at a constant current of 0.33 C at 45° C. and discharged to 3.0 V at a constant current of 0.33 C as 1 cycle. After 200 cycles of charge and discharge, the capacity retention rate was calculated as the ratio of the capacity after 200 cycles to the initial capacity.

[0145] [Table 2]

[0146] Initial capacity (Ah) Capacity retention rate (%) Example 1 1.98 92.8 Example 2 1.95 91.9 Example 3 1.90 91.0 Comparative Example 2 1.32 64.3

[0147] Referring to Table 2, it was confirmed that the lithium secondary batteries of Examples 1 to 3 exhibited excellent capacity characteristics and capacity retention rates compared to the lithium secondary battery manufactured in Comparative Example 2. This is expected to be because the impregnation properties of the flame retardant electrolyte in Examples 1 to 3 were excellent due to the zeta potential and dispersibility of the polymer particles contained in the porous coating layer.

[0148] Experimental Example 3 - Short Circuit Prevention Effect

[0149] The insulation resistance of each of the lithium secondary batteries manufactured in Examples 4 and 5 and Reference Example 1 was measured to evaluate the short-circuit prevention effect.

[0150] Specifically, the insulation resistance at 50 V of each of the lithium secondary batteries manufactured in Examples 4 and 5 and Comparative Example 1 was measured using a Hioki insulation resistance meter, and the results are shown in Table 3 below.

[0151] [Table 3]

[0152] Insulation resistance (ohm) Example 4 <![CDATA[50×10 8 ]]> Example 5 <![CDATA[50×10 8 ]]> Reference Example 1 <![CDATA[6×10 8 ]]>

[0153] Referring to Table 3, it was confirmed that the lithium secondary batteries of Examples 4 and 5 had excellent short circuit prevention effects due to the additional formation of the insulating layer.

Claims

1. A lithium secondary battery comprising: an electrode assembly comprising an electrode and a porous coating formed on the electrode; and A flame retardant electrolyte containing a flame retardant solvent having a flash point of 100°C or more or having no flash point and a lithium salt, in, The porous coating layer comprises polymer particles or ceramic particles having an absolute value of zeta potential of 25 mV or more.

2. The lithium secondary battery according to claim 1, wherein: The polymer particles include at least one selected from the group consisting of polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate and polyphenylene sulfide.

3. The lithium secondary battery according to claim 1, wherein: The ceramic particles include at least one selected from the group consisting of boehmite, Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5 and MnO.

4. The lithium secondary battery according to claim 1, wherein: The particle size of the polymer particles or ceramic particles is 50 nm to 3 μm.

5. The lithium secondary battery according to claim 1, wherein: The porous coating layer includes a polymer binder and the polymer particles or ceramic particles dispersed on the polymer binder.

6. The lithium secondary battery according to claim 5, wherein: The porous coating comprises a polymer binder:polymer particles or ceramic particles in a weight ratio of 5:95 to 40:

60.

7. The lithium secondary battery according to claim 1, wherein: The porous coating layer has a thickness of 5 to 50 μm and includes a plurality of pores having a diameter of 10 nm or more.

8. The lithium secondary battery according to claim 1, wherein: The flame retardant solvent includes at least one organic solvent having a functional group selected from the group consisting of a sulfone-based functional group, a fluorine-containing functional group, a phosphorus-containing functional group, and a nitrile-based functional group.

9. The lithium secondary battery according to claim 1, wherein: The flame retardant solvent includes at least one organic solvent selected from the group consisting of sulfone compounds, nitrile compounds, phosphoric acid compounds and fluorine-substituted carbonate compounds.

10. The lithium secondary battery according to claim 9, wherein: The sulfone compound includes at least one selected from the group consisting of sulfolane, ethyl methyl sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl isopropyl sulfone, ethyl isobutyl sulfone, isopropyl isobutyl sulfone, isopropyl sec-butyl sulfone and butyl isobutyl sulfone.

11. The lithium secondary battery according to claim 9, wherein: The nitrile compound includes at least one selected from the group consisting of malononitrile, succinonitrile, glutaronitrile, adiponitrile, suberonitrile and sebacononitrile.

12. The lithium secondary battery according to claim 9, wherein: The phosphoric acid compound includes at least one selected from the group consisting of dimethyl methylphosphonate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl ethylphosphonate, dimethyl methylphosphonate, (2-methoxyethoxy)methylphosphonate, diethyl (2-methoxyethoxy)methylphosphonate and triphenyl phosphate.

13. The lithium secondary battery according to claim 9, wherein: The fluorine-substituted carbonate compound includes at least one selected from the group consisting of bis(2,2,3,3-tetrafluoropropyl) carbonate, methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, propyl 2,2,2-trifluoroethyl carbonate, methyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, ethyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoroisopropyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolane-2-one and bis(2,2,3,3-pentafluoropropyl) carbonate.

14. The lithium secondary battery according to claim 1, wherein: The lithium salt includes LiN(SO2CF3)2.

15. The lithium secondary battery according to claim 1, wherein: The flame retardant electrolyte contains a lithium salt at a concentration of 0.5M to 6M.

16. The lithium secondary battery according to claim 1, wherein: The electrode assembly comprises: a positive electrode having a positive electrode tab; a negative electrode having a negative electrode tab; and the porous coating layer formed on the positive electrode or the negative electrode so as to be arranged between the positive electrode and the negative electrode, and The method further includes an insulating layer covering the conductive surface of the negative electrode at a position corresponding to the positive electrode tab.

17. The lithium secondary battery according to claim 16, wherein: The insulating layer covers the negative electrode side surface corresponding to the positive electrode tab and the exposed surface of the negative electrode surface facing the positive electrode where the porous coating layer is not formed.

18. The lithium secondary battery according to claim 16, wherein: The porous coating layers are formed on the positive electrode and the negative electrode, respectively, wherein the porous coating layer formed on the negative electrode and the porous coating layer formed on the positive electrode are in contact with each other.

19. A method for manufacturing a lithium secondary battery, the method comprising the following steps: forming a porous coating layer including polymer particles or ceramic particles having a zeta potential of 25 mV or more on the electrode; forming an electrode assembly including an electrode coated with the porous coating layer; and The electrode assembly is impregnated with a flame retardant electrolyte including a flame retardant solvent having a flash point of 100° C. or more or having no flash point and a lithium salt.

20. The method for manufacturing a lithium secondary battery according to claim 19, further comprising: The polymer particles or ceramic particles are subjected to plasma treatment to adjust the absolute value of the zeta potential to be greater than 25 mV.

21. The method for manufacturing a lithium secondary battery according to claim 19, wherein: Forming the porous coating layer includes applying a slurry containing the polymer particles or ceramic particles, a polymer binder and a liquid medium onto the electrode and drying it.

Citation Information

Patent Citations

  • Compound and organic light emitting device including the same

    KR1020220069165A

  • Mask having improved shut-off function for harmful component

    KR1020220073089A

  • Multiple fluid delivery system with multi-use disposable set and features thereof

    KR1020230061581A